The Comparison of the Prior Knowledge of First Grade Students regarding the Ability to Identify the Initial and Final Sounds, Name the Letters of the Alphabet, Read and Write (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
The phonological awareness ability affects reading and writing. At the beginning of the 1st grade, students have various prior knowledge in the areas of phonological awareness, reading and writing. We wondered about the possible consequences in the field of children's literacy after the pandemic. The purpose of the empirical research was to assess and compare the prior knowledge of students at the beginning of the 1st grade before the systematic literacy instruction regarding the ability to identify the initial and final sounds in a word, perceive and name the letters of the alphabet, read words, write letters and words before and after the pandemic. We individually assessed 514 first-graders. The first group of students was assessed in 2017 and the second in 2023. Differences between groups of students were analysed using a t-test for independent samples. The results indicate that students' prior knowledge has been decreasing, therefore, changes are necessary.